DNA hybridisation of routinely processed tissue for detecting HPV DNA in anal squamous cell carcinomas over 40 years. Issue 2 (February 1990) - Scholefield, J H; McIntyre, P; Palmer, J G; Coates, P J; Shepherd, N A; Northover, J M
Abstract : To study possible changes in the incidence of human papillomavirus (HPV) associated anal squamous cell carcinomas (SCC) a simple, rapid, and sensitive technique (alkaline hydrolysis) to permit DNA hybridisation from formalin fixed, paraffin wax embedded tissue was developed. The sensitivity and specificity of the technique were established by comparison with Southern blot analysis and in situ hybridisation on the same tissue specimens. Ninety tissue specimens in a single analysis were examined using this technique. Alkaline hydrolysis was applied to fixed tissue samples which showed a two-fold increase over the past 10 years in the percentage of anal cancers containing HPV type 16 DNA when compared with the previous 30 years using 207 cases of anal cancer collected over a 40 year period. This method has several advantages over the polymerase chain reaction as it is simple, relatively inexpensive, and may be widely applied to the detection and quantification of DNA sequences, including cellular oncogenes.